DIGITAL INFRASTRUCTURE AND SMART MONITORING SYSTEMS ON THE UKC RAILWAY: PROSPECTS FOR AI AND IOT INTEGRATION (International journal of artificial intelligence, 2025)
The Uzbekistan–Kyrgyzstan–China (UKC) railway corridor is poised to become a cornerstone of regional connectivity in Central Asia. As the global logistics landscape evolves, traditional railway infrastructure must be supplemented with smart, technology-driven systems. Emerging technologies such as artificial intelligence (AI), the Internet of Things (IoT), and cloud-based platforms provide powerful tools for transforming freight monitoring, asset management, and operational efficiency.